2017
DOI: 10.1109/tnsre.2016.2550864
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Electrotactile Feedback With Spatial and Mixed Coding for Closed-Loop Control of Grasping Force in Hand Prostheses

Abstract: Abstract-Providing somatosensory feedback to the user of a myoelectric prosthesis is an important goal since it can improve the utility as well as facilitate the embodiment of the assistive system. Most often, the grasping force was selected as the feedback variable and communicated through one or more individual single channel stimulation units (e.g., electrodes, vibration motors). In the present study, an integrated, compact, multichannel solution comprising an array electrode and a programmable stimulator w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 40 publications
(70 reference statements)
1
98
1
Order By: Relevance
“…It has been shown that sensory feedback improves grasping control and performance with myoelectric hand prostheses in inexperienced users (10,11). Both invasive and non-invasive sensory feedback systems are under development (2,9,(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…It has been shown that sensory feedback improves grasping control and performance with myoelectric hand prostheses in inexperienced users (10,11). Both invasive and non-invasive sensory feedback systems are under development (2,9,(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Therefore, the provision of feedback improved the quality of force control in both accuracy (MAE) and precision (STDAE). Importantly, contrary to previous studies, 10,13 the present experiment included a realistic task, in which the subjects needed to generate four levels of force in a random order (as when grasping a sequence of objects in real life). At the same time, the feedback was transmitted using a practically relevant method, i.e., a multichannel electrotactile interface implementing a low-resolution feedback (6 discrete levels).…”
Section: Discussionmentioning
confidence: 99%
“…Since the two coding schemes are perceptually separated (spatial localization versus frequency perception), it is likely that the SR for the mixed coding including combined spatial and frequency modulation would not be substantially different from that obtained for the single coding, i.e., spatial only or frequency only. We base this assumption on the results from our recent study [55], where mixed spatial (5 levels) and frequency (3 levels) coding was tested and the overall SR for the 15 codes (5×3) was 87%, with the marginal SR of 93% and 95% for the spatial and frequency levels. This was similar SR to that obtained for 6 spatial and 3 frequency levels in the present study (88% and 99%, respectively).…”
Section: Discussionmentioning
confidence: 99%